The relationship between depression and sexual satisfaction: An equation model analysis - Maedeh Khakkar; Ashraf Kazemi (Journal of Education and Health Promotion, 2023)
BACKGROUND: The relationship between depression and sexual satisfaction in middle-aged women has been reported previously. However, there is insufficient evidence that depression is related to sexual satisfaction or that sexual satisfaction is related to depression. This study evaluated the relationship between depression and sexual satisfaction in middle-aged women by evaluating the equation model analysis of the two models. MATERIALS AND METHODS: This cross-sectional study was conducted on 190 middle-aged women in Isfahan, Iran, in 2021. Sexual satisfaction dimensions were evaluated using self-report women's sexual satisfaction questionnaire. Also, the depression scale of the general health questionnaire was used to measure of the depression level. Research data were analyzed using a multivariate linear regression test. Also, the fit of the model was evaluated using Amos software. RESULTS: The results showed that depression score had an inverse relationship with sexual satisfaction in the relational concern dimension (Beta = −0.27, P = 0.006, CI: −0.11 to − 0.86). Model fit evaluation showed that the sexual satisfaction-depression model had a better fit than the depression-sexual satisfaction model (CMIN/DF = 1.123, P = 0.64). CONCLUSION: The results showed that depression in middle-aged women is related to the relational concern. It is necessary to consider counseling programs to solve sexual relationship concerns in middle-aged women's mental health promotion programs.